1994
DOI: 10.1111/j.1440-1754.1994.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and drug usage in parents soon after stillbirth, neonatal death or SIDS

Abstract: The behaviour of bereaved parents with respect to their drug and alcohol ingestion was examined 2 months following the loss of an infant from stillbirth (SB) neonatal death (NND) or sudden infant death syndrome (SIDS). Responses from bereaved families (99 SB, 109 NND, 52 SIDS) were compared with 252 control families (who had a liveborn infant). There was no difference in self-medication using aspirin as the example. The use of sedative drugs was significantly higher in all bereaved mothers (but especially the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Furthermore, similar MI risks in the two cohorts were seen during the first 6 years of follow-up, indicating that the two groups had a comparable MI risk at baseline. The bereaved parents could possibly develop more risky lifestyles, [15][16][17] which may be one of the possible causal pathways for the association. 5,7 The study could be confounded by genetic factors modifying both the risk of cardiovascular diseases and the cause of specific childhood deaths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, similar MI risks in the two cohorts were seen during the first 6 years of follow-up, indicating that the two groups had a comparable MI risk at baseline. The bereaved parents could possibly develop more risky lifestyles, [15][16][17] which may be one of the possible causal pathways for the association. 5,7 The study could be confounded by genetic factors modifying both the risk of cardiovascular diseases and the cause of specific childhood deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Bereaved parents often experience numerous forms of psychological stress, such as depression, despair, anxiety, guilt, anger, hostility, hopelessness, as well as preoccupation with thoughts of the deceased child. [12][13][14][15] They may have more somatic complaints and interpersonal difficulties and react with more adverse health behaviors. [12][13][14][15][16][17] It has been suggested that factors related to the nature of the death, personal characteristics, and interpersonal contexts could modify the effect of the bereavement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bereaved parents may have more somatic complaints, interpersonal difficulties and react with more adverse health behaviors [18][19][20][21]. However, so far no study of sufficient size has investigated the importance of parental bereavement in relation to stroke or other forms of cerebrovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The death of a child is one of the most extreme stressors [17,18], and this life event may lead to depression, despair, anxiety, guilt, anger, hostility and hopelessness [18][19][20][21]. Bereaved parents may have more somatic complaints, interpersonal difficulties and react with more adverse health behaviors [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%